Regulatory Function of Polyamine Oxidase-Generated Hydrogen Peroxide in Ethylene-Induced Stomatal Closure in Arabidopsis thaliana - Zhi-hui HOU; Guo-hua LIU; Li-xia HOU; Lan-xiang WANG; Xin LIU (Journal of Integrative Agriculture)
Hydrogen peroxide (H2O2) is an important signaling molecule in ethylene-induced stomatal closure in Arabidopsis thaliana. Early studies on the sources of H2O2 mainly focused on NADPH oxidases and cell-wall peroxidases. Here, we report the involvement of polyamine oxidases (PAOs) in ethylene-induced H2O2 production in guard cells. In Arabidopsis epidermal peels, application of PAO inhibitors caused the failure of ethylene to induce H2O2 production and stomatal closure. Results of quantitative RT-PCR analysis and pharmacological experiments showed that AtPAO2 and AtPAO4 transcripts and activities of PAOs were both induced by ethylene. In transgenic Arabidopsis plants over-expressing AtPAO2 and AtPAO4, stomatal movement was more sensitive to ethylene treatment and H2O2 production was also significantly induced. The increased H2O2 production in the transgenic lines compared to the wild-type plants suggests that AtPAO2 and AtPAO4 probably are involved in ethylene-induced H2O2 production. Several factors which induce stomatal closure such as dehydration and high salinity all enhanced the expression of AtPAO2 and AtPAO4 to different degrees. Moreover, GFP-AtPAOs fusion protein localized in the nucleus, cytoplasm, and cell wall of the guard cells. Therefore, our results strongly indicated that PAO is a source of H2O2 generation in Arabidopsis guard cells and plays crucial roles in stomatal movement.